Analysis Student-Centered Learning Practice, Driving School Program At SDN 06 Bungku, Morowali Regency - Rus'an Rus'an; Retoliah Dahlan; Sitti Nadirah; Aniati Aniati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study analyzes the relationship between the administrative readiness of the Independent Curriculum learning planning administration and pedagogical transformation towards student-centered learning (SCL) and the strengthening of the Pancasila Student Profile in the SDN 06 Bungku Driving School Program, Morowali. Using a qualitative–quantitative descriptive approach, data were collected from 10 teachers through documentation of planning tools and classroom practice questionnaires. The results showed that the planning administration's readiness was in the good and excellent categories, supporting the implementation of differentiation-based SCL, formative assessment, and projects to strengthen the Pancasila Student Profile. The novelty of this study lies in the analytical mapping of the direct relationship between the quality of planning for the Independent Curriculum and the success of SCL practice in driving elementary schools, as well as in identifying weak areas, such as the optimization of learning resources, diagnostic assessment, and project-based learning. The main contribution of this research is to provide practical recommendations for developing more effective SCL by strengthening teachers' capacity in pedagogical planning and cross-stakeholder collaboration.